PERAN MADRASAH DALAM MEMBENTUK KEHIDUPAN PENDIDIKAN HUMANIS, INKLUSIF, DAN RELIGIUS - Mentari, Luluk Kurnia (LP. Ma'arif Janggan Magetan, 2020)
Abstract: Madrasa is a place or educational institution to study Islamic knowledge, science, and other expertise in a directed, guided, and controlled manner. The approach used in this research is a qualitative approach techniques of using collection data, namely library technique. The results of the analysis show that madrasa have an important role, that is as an educational institution in advancing education and improving the quality of educational organizer that are humanistic, inclusive, and religious. Some things that can be done by the madrasa to achieve the role of madrasa in form the life of humanist, inclusive, and religious education as follows: 1) Madrasa prepares adequate facilities and infrastructure for the teaching and learning process; 2) Madrasas prepares of quality education organizeror human resources in appropriate with competencies; 3) Madrasa prepares curriculum, administration, extracurricular activities, and its management system are formulated and implemented for the benefit of students including ABK; 4) Madrasa must provide the conditions of class that are warm, friendly, accept diversity and respect differences; 5) Madrasa must be prepared to manage heterogeneous classes by applying curriculum and learning that is individualized; 6) The teacher must be implemented interactive learning. Madrasah merupakan tempat atau lembaga pendidikan untuk mempelajari ajaran Islam secara terarah, terpimpin, dan terkendali. Hasil penelitian kualitatif ini menemukan bahwa madrasah memiliki peranan yang penting yaitu sebagai lembaga pendidikan dalam memajukan pendidikan serta meningkatkan kualitas penyelenggara pendidikan yang bersifat humanis, inklusif, dan religius. Beberapa hal yang dapat dilakukan oleh pihak madrasah untuk mencapai peran madrasah dalam membentukkehidupan pendidikan humanis, inklusif, dan religius sebagai berikut : 1) Madrasah mempersiapkan sarana dan prasarana yang memadai untuk proses belajar mengajar; 2)Madrasah menyiapkan penyelenggara pendidikan atau SDM yang berkualitas sesuai dengan kompetensi; 3) Madrasah mempersiapkan kurikulum, administrasi, kegiatan ekstrakurikuler, serta sistem pengelolaannya dirumuskan dan dilaksanakan demi kepentingan peserta didik termasuk ABK; 4) Madrasah harus menyediakan kondisi kelas yang hangat, ramah, menerima keaneka-ragaman dan menghargai perbedaan; 5) Madrasah harus siap mengelola kelas yang heterogen dengan menerapkan kurikulum dan pembelajaran yang bersifat individual; 6) Guru harus menerapkan pembelajaran yang interaktif.